DYSLIPIDEMIA ROLE IN THE DEVELOPMENT OF METABOLIC SYNDROME - M. V. Antonyuk; V. V. Knyshova (Российский кардиологический журнал, 2011)
The paper analyses the role of lipid and carbohydrate metabolism disturbances in the development of metabolic syndrome (MS), based on the prevalence of MS among 554 individuals with varying body weight. Among participants with normal body weight and overweight individuals, dyslipidemia was registered in 85–88%. Among patients with Stage I–II obesity, the most prevalent MS component was arterial hypertension (75–80%). Hyperglycemia, the diagnostic criterion of MS, was less prevalent than hyperinsulinemia or insulin resistance, which complicated early MS diagnostics. Overall, participants with normal body weight or overweight individuals demonstrated higher prevalence of lipid vs. carbohydrate metabolism disturbances. Further research is needed to clarify the pathogenetic role of dyslipidemia in MS development.